1999
DOI: 10.1097/00042737-199902000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt versus endoscopic sclerotherapy for the prevention of variceal rebleeding after recent variceal hemorrhage

Abstract: Variceal hemorrhage continues to be a major cause of morbidity and mortality in cirrhotic patients. Transjugular intrahepatic portosystemic shunt (TIPS) is gaining wide acceptance as a treatment for several complications of portal hypertension. The aim of the current randomized study was to compare the transjugular shunt and endoscopic sclerotherapy (ES) for the prevention of variceal rebleeding (VB) in cirrhotic patients. Forty-six consecutive cirrhotic patients with variceal bleeding were randomly allocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 14 publications
1
47
0
2
Order By: Relevance
“…Overall, 11 randomized trials involving 811 patients [13][14][15][16][23][24][25][26][27][28][29] met the inclusion criteria. Eight were published as full articles in peer-reviewed journals, [13][14][15][16][23][24][25][26] and 3 were published only as abstracts [27][28][29] (Table 2). Agreement between reviewers for the selection of relevant articles was 100%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, 11 randomized trials involving 811 patients [13][14][15][16][23][24][25][26][27][28][29] met the inclusion criteria. Eight were published as full articles in peer-reviewed journals, [13][14][15][16][23][24][25][26] and 3 were published only as abstracts [27][28][29] (Table 2). Agreement between reviewers for the selection of relevant articles was 100%.…”
Section: Resultsmentioning
confidence: 99%
“…TIPS was compared with sclerotherapy alone in 5 studies, [13][14][15][16]26 with sclerotherapy plus propranolol in 3 studies 23,24,27 (sclerotherapy or ligation plus propranolol in one 23 ), and with ligation alone in 3 studies 25,28,29 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 TIPS is relatively easy to perform, quite safe, and causes a portal decompression similar to that achieved by surgical shunts. 3,4 Randomized controlled trials (RCTs) [5][6][7][8][9][10][11][12][13][14][15] and meta-analyses [16][17][18][19] have shown that TIPS is more effective than endoscopic therapy in preventing variceal rebleeding. However, some studies reported an increased in-cidence of encephalopathy following TIPS.…”
mentioning
confidence: 99%